Digitally enabled stakeholder collaboration for sustainable urban facilities management: insights from Abu Dhabi’s public sector - Abeer Alhammadi; Alex Opoku (Facilities, 2026)
Purpose This study aims to investigate how facilities management (FM) digital technologies impact stakeholder collaboration, how key sustainability drivers and collaboration affect sustainable building FM, and the moderating effect of digital technologies on sustainability drivers’ influence on sustainable building FM. It compares managers’ and users’ perspectives, providing empirical evidence from Abu Dhabi’s public buildings managed by the Department of Culture and Tourism and the Department of Municipalities and Transport. Design/methodology/approach Grounded in stakeholder theory, the study adopts a quantitative survey approach. Data were collected from 334 managers and users of Abu Dhabi public facilities and analysed using partial least squares structural equation modelling. Findings FM digital technology strongly enhances stakeholder collaboration, which positively influences sustainable building FM. Environmental management and site/location analysis also contribute directly to sustainable building FM. Digital technology demonstrates a weak but meaningful moderating effect on the relationship between environmental management and sustainable building FM, while no moderating effect is observed for site/location analysis. Facility users perceive a stronger link between digital technology and collaboration than facility managers. Practical implications Public facilities should prioritise community-centric digital platforms to enhance collaboration and support SDGs 3 (Good Health and Well-being), 9 (Industry, Innovation and Infrastructure) and 11 (Sustainable Cities and Communities). Manager training is essential to align perceptions and foster participatory FM towards resource efficiency and urban resilience. Originality/value This study advances urban FM sustainability research by empirically integrating managers’ and users’ perspectives in a public sector context, clarifying where digital technologies strengthen, or fail to strengthen, sustainability mechanisms, and highlighting their role in bridging perceptual differences in Abu Dhabi.